Conceptual Framework of Social Education: a Systematic Study - Fateme Kohanpor; Maryam Baradaran; Nikoo Dialameh (علوم تربیتی از دیدگاه اسلام)
The aim of this research is to provide a conceptual framework of social education. For this purpose, the systematic review method has been used. In the stage of data collection, in the first step, a search was made with the keyword of social education in four reputable and famous domestic databases in the humanities (Ganj, Human, Jihad Academia and Alm-Net) and the number of 784 research works was found. Related (theses and articles) were identified. In the next step, 61 works were selected by examining the researches in the framework of certain criteria during a systematic process. In the data analysis stage, firstly, using the scope study method, the selected researches in social education were described and categorized, and the volume of studies and the main themes of the subject area were shown. After that, the conceptual network method of information, which is a combination of various types of research, was used, and as a result, four general components in social education were obtained, which are: "Human relations based on divine ethics" with two indicators of  justice and benevolence. "Compassionate encounter with cultural intellectual heritage and social issues", "right-oriented consensus", "social participation", each of which has sub-components in the three domains of "cognitive", "motivational" and "behavioral", and their relationship is also displayed in a model.